Integrated Multidisciplinary Diabetes Care in Hospital: A Systematic Review (Universitas Negeri Semarang, 2021)
A multidisciplinary team approach in an integrated practice unit has been proposed as part of value-based health care in hospital diabetes management strategy. The objective of this study is to assess the economic impact of integrated multidisciplinary team implementation compared to conventional care in the management of Type 2 Diabetic patients in a hospital setting. This study is a systematic literature review that was conducted using the following databases: CINAHL, Medline (PubMed), ProQuest, EMBASE, and Cochrane library. The outcome included economical aspects of multidisciplinary team implementation. Quality appraisal of the studies was undertaken using the CASP checklist. From five included studies, there are four cost-effectiveness studies and one retrospective study using ABC costing method. All five studies indicated a positive trend toward the intervention groups. The cost of each QALY ranged from 2443 EUR – 5031 EUR (5993USD). The total cost spent for the implementation of a multidisciplinary team compared to the conventional method were varied among the studies. However, after the calculation projected to the cost of the complication models and QALY gained on each study, the implementation cost was found to be cost-effective and cost-saving in the treatment group. Therefore, the implementation of an integrated multidisciplinary team is potentially economically beneficial for type 2 diabetes patients management in hospitals.